Antibiotics usage practices in aquaculture in Bangladesh and their associated factors - Chowdhury, S.; Rheman, Shafiq; Debnath, N.; Delamare-Deboutteville, Jerome; Akhtar, Z.; Ghosh, S.; Parveen, S.; Islam, K.; Islam, M.A.; Rashid, M.M.; Khan, Z.H.; Rahman, M.; et al. (Elsevier, 2022)
Background Irrational and inappropriate use of antibiotics in aquaculture can contribute to the development of antibiotic resistance.